Congenital Leukemia: A Case Report - Quddush, ASM Ruhul; Md Kamruzzaman, -; Md Badruzzaman, -; Jahan, Shahanaz; Sattar, Shamima (Community Based Medical Journal, 2015)
A 5 week-old infant presented with fever and pallor for two weeks, reluctant to feed for one week and passage of bloody stool one time two days back. Child was found less active and severely anaemic with hepato-splenomegaly. Peripheral blood film showed marked leukocytosis with many immature cells which are mostly blast cell resembling lymphoblast containing one-two nucleoli. Bone marrow aspiration revealed findings suggestive of acute lymphoblastic leukemia. Other possibilities like neonatal sepsis and TORCH infection were ruled out and a final diagnosis of congenital leukemia was made. CBMJ 2015 July: Vol. 04 No. 02 P: 55-57